2010
DOI: 10.1111/j.1475-682x.2009.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Media Framing of Body Burdens: Precautionary Consumption and the Individualization of Risk

Abstract: The accumulation of chemicals in human bodies and ecosystems represents a universal environmental and technological risk. As yet, little attention has been paid to media coverage of “body burdens,” the internal contaminant load carried by most organisms in the industrialized world. Using a sociology of risk perspective, this article analyzes the framing of chemical bioaccumulation in Canadian newspaper articles from 1986 to 2006. In later years, articles employ frames that reinforce an individualization of ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…Increasing awareness of the potential harms of flame retardant exposure in pregnancy allows the individual woman to be aware of exposure to BFRs and to make informed decisions to reduce exposure to BFRs if possible [8]. However, lack of information sources on routes of exposure and potential harms of flame retardants in consumer products makes it difficult for pregnant women and women contemplating pregnancy to make such informed choices regarding how and to what extent they may decrease their exposure to flame retardants [26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…Increasing awareness of the potential harms of flame retardant exposure in pregnancy allows the individual woman to be aware of exposure to BFRs and to make informed decisions to reduce exposure to BFRs if possible [8]. However, lack of information sources on routes of exposure and potential harms of flame retardants in consumer products makes it difficult for pregnant women and women contemplating pregnancy to make such informed choices regarding how and to what extent they may decrease their exposure to flame retardants [26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…Instead, we would point to earlier research on conventional (non-ethical) consumption that has identified motivations that can be usefully applied to the case of organic food consumption: specifically, Thompson's (1996) concept of caring consumption, Miller's (1998) concept of "shopping as sacrifice" (Miller, 1998), and MacKendrick's (2010) concept of "precautionary consumption" (MacKendrick, 2010). What these three perspectives on consumption share is a framing of consumption as underscored by a sense of social connection and caring for others for whom consumers, particularly women, are personally responsible.…”
Section: Discussionmentioning
confidence: 99%
“…EHJM biomonitoring informs the public and policymakers about biomonitoring. These efforts have opened up a space for national dialog about pervasive human exposures to environmental chemicals and the need for chemical policy reform (Lautenberg 2011).…”
Section: Discussionmentioning
confidence: 99%